Immunometabolism and atherosclerosis: perspectives and clinical significance: a position paper from the Working Group on Atherosclerosis and Vascular Biology of the European Society of Cardiology. Issue 9 (22nd June 2019) - Ketelhuth, Daniel F J; Lutgens, Esther; Bäck, Magnus; Binder, Christoph J; Van den Bossche, Jan; Daniel, Carolin; Dumitriu, Ingrid E; Hoefer, Imo; Libby, Peter; O'Neill, Luke; Weber, Christian; Evans, Paul C
Abstract: Inflammation is an important driver of atherosclerosis, and the favourable outcomes of the Canakinumab Anti-inflammatory Thrombosis Outcome Study (CANTOS) trial revealed the large potential of anti-inflammatory drugs for the treatment of cardiovascular disease, especially in patients with a pro-inflammatory constitution. However, the complex immune reactions driving inflammation in the vascular wall in response to an atherosclerotic microenvironment are still being unravelled. Novel insights into the cellular processes driving immunity and inflammation revealed that alterations in intracellular metabolic pathways are strong drivers of survival, growth, and function of immune cells. Therefore, this position paper presents a brief overview of the recent developments in the immunometabolism field, focusing on its role in atherosclerosis. We will also highlight the potential impact of immunometabolic markers and targets in clinical cardiovascular medicine. Graphical Abstract: